2021
DOI: 10.17645/mac.v9i2.3851
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Voice and Online Space: Expressions of Feminism on Social Media in Spain

Abstract: Feminism’s current momentum, encouraged by movements such as #NiUnaMenos or #MeToo, has caused many social media agents to adopt some degree of feminism as a part of their online image or personal brand. ‘Being a feminist,’ for some, has become a marketing strategy in times of great polarisation between progressive forces and a reactionary backlash against feminism. The appropriation of feminism by the global market challenges public opinion, media, and academia to think and rethink feminism, and to consider w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 54 publications
0
9
0
2
Order By: Relevance
“…Data mainly came from ForoCoches ( https://forocoches.com/ ), a well known and influential Spanish forum. 14 15 The administrators of ForoCoches granted us access to publish a post on their website for this research. We also posted the survey on other websites such as Reddit and 4Chan.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data mainly came from ForoCoches ( https://forocoches.com/ ), a well known and influential Spanish forum. 14 15 The administrators of ForoCoches granted us access to publish a post on their website for this research. We also posted the survey on other websites such as Reddit and 4Chan.…”
Section: Methodsmentioning
confidence: 99%
“…We collected data anonymously using a cross sectional design, with an online survey distributed on several platforms. Data mainly came from ForoCoches (https://forocoches.com/), a well known and influential Spanish forum 1415. The administrators of ForoCoches granted us access to publish a post on their website for this research.…”
Section: Methodsmentioning
confidence: 99%
“…En la actualidad, producto de la tecnología, mediante las redes sociales y con el uso del YouTube, Instagram y Twitter, Tiktok o Twitch, surgen nuevos tipos de interacciones que muchas veces constituyen acciones de violencia inmaterial sobre la mujer, con alcance sin límites tal como permiten Facebook y Twitter, Instagram) entre otros (Willem & Tortajada, 2021).…”
Section: Resultsunclassified
“…These studies do not always distinguish between its various branches, even though prior research has identified a division within feminism based on either liberal versus radical or trans-inclusive versus trans-exclusive viewpoints [34,80,95]. Gender-Critical Feminism (GCF), also derogatorily known as trans-exclusionary radical feminism (TERF), views transgender people's activism and visibility as a possible threat to women's rights and spaces due to their challenging of the binary understanding of sex and gender [40,83].…”
Section: Background and Related Workmentioning
confidence: 99%